PERAN PELATIHAN KERJA, KOMPETENSI KARYAWAN, DAN DISPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT KANAAN GLOBAL INDONESIA - Alima Nur Fadillah; Fathimatuzzahro; Leny Arsita Sari; Ni Made Lintang Purnaasa; Rayhan Gunaningrat (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the influence of job training, employee competency, and work discipline on employee performance at PT Kanaan Global Indonesia. The study employed a quantitative approach with a survey method. The sampling technique used was saturated sampling, with the entire employee population of 30 employees being sampled. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that employee competency and work discipline had a positive and significant effect on employee performance, while job training had no significant effect partially. However, all three variables simultaneously had a significant effect on employee performance.